Cutaneous Adnexal Adenocarcinoma: Genomic Analysis and Successful HER2-targeted Therapy of Metastatic Disease - Yui Hirano-Lotman; Yoshihiro Ishida; Yuichiro Endo; Seishi Ogawa; Kenji Kabashima (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)